Proceedings of the 4th International Conference on Sustainable Innovation 2020-Accounting and Management (ICoSIAMS 2020) 2021
DOI: 10.2991/aer.k.210121.017
|View full text |Cite
|
Sign up to set email alerts
|

The Job Stress as a Mediation Between Role Conflict and Employee Performance

Abstract: There has been continuous scrutiny of employee performance as it is a measure of both employee and organizational success. However, the determinants of employee performance are not yet convincing. Two inconclusive determinants of employee performance identified from the literature are role conflict and job stress. This study examines the mediating role of job stress between role conflict and employee performance. Primary data were collected from 102 employees of the Regional Financial and Asset Management Offi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The results of these calculations obtained the value of Q 2 is 0.879 so it can be concluded that the model has very good predictive relevance. Thus, it can be explained that 87.9 percent of the variation in employee performance is influenced by work-family conflict, and motivation, while the remaining 12.1 percent is influenced by other variables not examined in this study Pradhan & Jena, 2017;Rahayu & Hidayat, 2021;Rahyuda & MSIE, 2016).…”
Section: Evaluation Of Structural Model or Inner Modelmentioning
confidence: 69%
“…The results of these calculations obtained the value of Q 2 is 0.879 so it can be concluded that the model has very good predictive relevance. Thus, it can be explained that 87.9 percent of the variation in employee performance is influenced by work-family conflict, and motivation, while the remaining 12.1 percent is influenced by other variables not examined in this study Pradhan & Jena, 2017;Rahayu & Hidayat, 2021;Rahyuda & MSIE, 2016).…”
Section: Evaluation Of Structural Model or Inner Modelmentioning
confidence: 69%
“…As highlighted earlier, work stress focuses on extreme stress and burnout. The Thus, the theoretical model can be setup as the following This theoretical model is similar to the theoretical model highlighted by Rahayu and Hidayat (2021) in explaining the relationship between role conflict and employee performance, with job stress as the mediator. The key difference is that the model refers to two dependent variables: academic and workplace performance.…”
Section: Methodsmentioning
confidence: 99%
“…When individuals face stress due to various work conditions and fail to cope with stress then it results in burnout (Pandey & Pal, 2020). When employees feel depressed or burdened when completing their work, their performance will be disrupted (Rahayu & Hidayat, 2021). Most employees who work in the city and live outside the city face a lot of stress from home to work, having compound stress due to traffic.…”
Section: The Effect Of Work Stress On Employee Performancementioning
confidence: 99%